USERS’ PERSONALITIES AND GENDER EFFECTS ON SOCIAL MEDIA USAGE DURING THE COVID-19 PANDEMIC - Diyana Mohd Reffal; Nursafwah Tugiman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The Covid-19 epidemic has made Malaysian consumers between the ages of 19 and 30 were highly dependent on social media. This is due to the fact that all activities, including employment and education necessities, are conducted online on social media platforms like Facebook and WhatsApp. This research propose that the negative or positive use of social media are depending on the personality of the user. Neuroticism, Extraversion, Openness, Conscientiousness, and Agreeableness are the five primary personalities according to The Big Five Personality Theory. This study examines the use of social media during the Covid-19 pandemic. There were 200 respondents who voluntarily engaged in this survey. The study found that Neuroticism increased by 0.814% based on time spent on social media, whereas Extraversion increased by 0.905%. In addition, the survey found that male respondents have a higher Neuroticism score (m=5.378) than female respondents (m=4.639), and that male respondents utilise social media more (m=5.781) than female respondents (m=5.574). To conclude, high institutions such as the government, universities, teachers, and students can benefit from this research regarding the negative health effects of excessive social media use.